2017
DOI: 10.1002/2016jc012419
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of the Arctic Ocean's double-diffusive staircase

Abstract: The Arctic Ocean thermohaline stratification frequently exhibits a staircase structure overlying the Atlantic Water Layer that can be attributed to the diffusive form of double‐diffusive convection. The staircase consists of multiple layers of O(1) m in thickness separated by sharp interfaces, across which temperature and salinity change abruptly. Through a detailed analysis of Ice‐Tethered Profiler measurements from 2004 to 2013, the double‐diffusive staircase structure is characterized across the entire Arct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(130 citation statements)
references
References 37 publications
10
119
1
Order By: Relevance
“…The distribution of the AW thermocline-averaged internal wave-driven turbulent heat flux ranges from ∼0.1 to ∼90 W/m 2 , with a geometric mean of ∼1 W/m 2 (Figure 13a). This peak value is 1 to 2 orders of magnitude larger than typical Arctic double-diffusive heat fluxes (Shibley et al, 2017) and is comparable to many other observed values of Arctic Ocean turbulent heat fluxes (see Table 1 and references therein). While the average value of F H appears typical, it is also important to consider the implications of anomalously high values evident in the skew symmetric shape of its distribution.…”
Section: Figure 12supporting
confidence: 85%
See 2 more Smart Citations
“…The distribution of the AW thermocline-averaged internal wave-driven turbulent heat flux ranges from ∼0.1 to ∼90 W/m 2 , with a geometric mean of ∼1 W/m 2 (Figure 13a). This peak value is 1 to 2 orders of magnitude larger than typical Arctic double-diffusive heat fluxes (Shibley et al, 2017) and is comparable to many other observed values of Arctic Ocean turbulent heat fluxes (see Table 1 and references therein). While the average value of F H appears typical, it is also important to consider the implications of anomalously high values evident in the skew symmetric shape of its distribution.…”
Section: Figure 12supporting
confidence: 85%
“…While the distribution of F H only depicts heat fluxes in turbulent regimes, it is also relevant and worthwhile to consider a hypothetical distribution of heat fluxes that also includes the nonturbulent regimes, and is thus representative of the study domain as a whole. For this purpose, we assume that F H is 0.1 W/m 2 everywhere Re b < 20, consistent with the order of magnitude of double-diffusive heat fluxes that Shibley et al (2017) observed in the Canada Basin. When the contributions from these nonturbulent environments are taken into account, we find that despite the fact that only ∼60% of our domain can be characterized as turbulent according to the Re b > 20 criterion, turbulent heat fluxes in these regions account for 96% of the net integrated heat flux over the whole study region.…”
Section: Figure 12mentioning
confidence: 95%
See 1 more Smart Citation
“…Recent observations have shown continental shelf break regions of the Arctic Ocean host significant barotropic tidal energy conversion (Rippeth et al, 2015), with evidence of greatly enhanced , and by implication mixing, over sloping topography in the presence of significant tides (e.g., D'Asaro & Morison, 1992;Fer et al, 2010;Padman & Dillon, 1991;Rainville & Winsor, 2008;Rippeth et al, 2015). This is in sharp contrast to much of the central Arctic Ocean that is found to be remarkably quiescent (e.g., Lincoln et al, 2016;Shibley et al, 2017). However, much of the Arctic Ocean lies poleward of the critical latitude and so the conversion of barotropic tidal energy to a freely propagating linear internal tide, over sloping topography, is suppressed by rotation.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of heat and salt fluxes can be made by considering the steady state energy balance for a layer (e.g., Hieronymus & Carpenter, ): ϵ=gαFθgβFS, which relates the dissipation of turbulent kinetic energy ϵ within a layer and the net buoyancy flux for large Rayleigh numbers (Rayleigh numbers are 108 for the Canada Basin layers; Shibley et al, ). Note that assumes that there is no large‐scale background shear which is a reasonable assumption given that the lateral density gradient in the Canada Basin at these depths is effectively 0.…”
Section: Theoretical Formulationmentioning
confidence: 99%